-5(2x+8)=-4(3x-11)

Simple and best practice solution for -5(2x+8)=-4(3x-11) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(2x+8)=-4(3x-11) equation:



-5(2x+8)=-4(3x-11)
We move all terms to the left:
-5(2x+8)-(-4(3x-11))=0
We multiply parentheses
-10x-(-4(3x-11))-40=0
We calculate terms in parentheses: -(-4(3x-11)), so:
-4(3x-11)
We multiply parentheses
-12x+44
Back to the equation:
-(-12x+44)
We get rid of parentheses
-10x+12x-44-40=0
We add all the numbers together, and all the variables
2x-84=0
We move all terms containing x to the left, all other terms to the right
2x=84
x=84/2
x=42

See similar equations:

| 5x=2x+6= | | 2/5x=-25 | | x-23=-38 | | 3x−2=2x+2 | | 3x+2=6x+13 | | x-(-17)=43 | | -7x+(x-5)=-11 | | 3•(x-5)=-18 | | 3(4s+9)=63 | | 205=53-x | | 3(2l+8)=54 | | (e-8)*9=36 | | (e-6)*5=25 | | 7x+2=121 | | 10+20+2x=60 | | 1/x=17 | | 15+12n=2(n-4) | | 11+4x=0 | | 15-3x=x+9 | | -1x=-21 | | 3(2y-8)=30 | | (x-1)(x-5)(x+4)=0 | | 13x2-11x-5=0 | | -2x+32=2 | | x2-457x+68=0 | | 42-2x=30 | | x2-18x+249=0 | | -x2+9x+20=0 | | -7x2+3x-54=0 | | 2x2+37x+48=0 | | 8x-7=3x-2 | | 8a=38+6a |

Equations solver categories